Physical and Social Drinking Contexts Changes Due to the Lockdown During the COVID-19 Pandemic Modified Alcohol Consumption in a Sample of Argentine College Students - Carreira Caro, Candela Sofía (Journal of drug issues, 2025)
Alcohol consumption is highly prevalent in college students, being important to identify risk factors for alcohol consumption. Thus, this work explored students' alcohol consumption and the influence of drinking contexts and how the lockdown modified drinking contexts and its influence on alcohol consumption. Argentinean college students (N = 1762; 74.8% women; Mean age = 23.25 ± 2.64) completed a survey that assessed alcohol consumption and related contexts before and during the lockdown. Latent Class Analysis identified 5 context-classes that showed different alcohol consumption patterns. A high percent of students drink alcohol in various contexts, but especially those related with social encounters with peers. Moreover, students who consume alcohol at social events with peers tend to have higher consumption rates per occasion and on a monthly basis. The confinement measures could have an effect on reducing alcohol use in college students, probably by modifying the drinking context of some students. college students consume alcohol extensively, which is worrying considering the health disturbances that it produces. Moreover, it is important to consider special situations such as the lockdown -that could modify contexts and its influence on consumption-to devise intervention strategies to reduce alcohol consumption.